2016
DOI: 10.1016/j.ophtha.2016.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Histologic Features with In Vivo Imaging of Reticular Pseudodrusen

Abstract: Reticular pseudodrusen represent subretinal deposits that extend through the outer nuclear layer, affect photoreceptor integrity, and are associated with retinal gliosis and RPE damage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
114
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(122 citation statements)
references
References 32 publications
7
114
1
Order By: Relevance
“…7073 An equivalent population has not yet been described in normal aged human eyes, although microglia appear in atrophic areas 61, 69, 70 and in association with advanced subretinal drusenoid deposits. 74 Alternatively, several mouse models involving targeted disruption of mechanistically diverse pathways also exhibit ‘sloughed’ RPE 7580 , supporting the concept that RPE stress responses are a final common pathway to multiple different stressors. What molecular signals prompt RPE to assume migratory behaviors in human GA eyes is unspecified.…”
Section: Discussionmentioning
confidence: 96%
“…7073 An equivalent population has not yet been described in normal aged human eyes, although microglia appear in atrophic areas 61, 69, 70 and in association with advanced subretinal drusenoid deposits. 74 Alternatively, several mouse models involving targeted disruption of mechanistically diverse pathways also exhibit ‘sloughed’ RPE 7580 , supporting the concept that RPE stress responses are a final common pathway to multiple different stressors. What molecular signals prompt RPE to assume migratory behaviors in human GA eyes is unspecified.…”
Section: Discussionmentioning
confidence: 96%
“…10 In a more recent histologic study, Greferath and colleagues reported SDD in the outer nuclear layer juxtaposed to photoreceptor outer segments, along with overlying photoreceptor disruption and loss. 46 Although Greferath reported a lack of choroidal changes in association with RPD, this study focused on cross-sections of larger vessels in the choroid and provided no quantitative flatmount studies or detailed endothelial immunohistochemical or electron microscopic methods that would be necessary to evaluate the integrity of the choriocapillaris.…”
Section: Discussionmentioning
confidence: 99%
“…This hypothesis is supported by experimental studies in mouse models, in which subretinal microglia are active in aging 59,60 compared to intermediate disease and worse in humans. 61, 62 Notably in human GA, pigmented cells resembling ‘sloughed’ and ‘intraretinal’ RPE express an inflammatory marker (CD163, a haptoglobin-hemoglobin scavenger) typical of bone marrow-derived macrophages, suggesting a new range of activities. 61 Transdifferentiation is the changing of a cell from one differentiated state to another.…”
Section: Discussionmentioning
confidence: 99%